Sugar Content and Consumption of Franchise Beverages as Risk Overweight Factors - Dika Betaditya; Gumintang Ratna Ramadhan; Yovita Puri Subardjo; Fishka Diah Betari; Ine Berlian Yustika (Sarana Ilmu Indonesia (salnesia), 2022)
Nowadays, the franchise business is growing very rapidly, one of which is sweet beverages. The characteristics of the berverages have a high sugar content that exceeds the recommended limit for daily consumption, which is 6-12 g. Excess sugar consumption can lead to being overweight. This study aimed to know the sugar content and total calories contained in franchise beverages. This research was an observational study with descriptive analysis design. The sugar content was tested using the Nelson-Somogyi method and total calories were tested using a bomb calorimeter. The number of beverage samples were 8 samples of drinks and toppings based on the best-selling drinks. The average total sugar contained in selected franchise beverages were 39,81 g/serving size and total calories were 389,75 kcal/serving size. The conclusion that total sugar contained in the selected drink topping was 2,47 g/serving size and total calories was 60,72 kcal/serving size. The average sugar content and total calories were exceeded the recommended daily sugar intake, so it was necessary to limit daily consumption of these drinks.